Scientific Management Theory: a Critical Review from Islamic Theories of Administration - Jafar Paramboor; Mohammed Borhandden Musah; Shafeeq Hussain Vazhathodi al- Hudawi (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2016)
Early management theory consisted of numerous attempts at getting to know some newcomers to industrial life at the end of the nineteenth century and the beginning of the twentieth century, in Europe and United States. As far as these newcomers were concerned, almost all fields of industry expected that they could open a new way of pattern in the area of conceptualizing the management field with new ideas and thoughts. One of these newcomers was the scientific management theory, the theory of Frederic Winslow Tylor (1896-1915). This paper is a critical review on scientific management theory looking from the descriptive and normative angles of Islamic theories of administration. Starting from the background of the author, and his theory, the paper highlights some of the criticisms arose from the West, followed by Islamic dimensions on the theory of administration, focusing on the individual and social aspects. The paper argues that the values should be taken from Islamic theories of administration which refers to the present world as well as hereafter. Further, some of the implications and possible areas of practicing Islamic theory of administration in higher education management are presented.